THE RISK OF KNOWLEDGE, SMOKING AND PATIENT'S CONTACT ON TUBERCULOSIS DISEASE IN PUUWATU HEALTH CENTRE IN KENDARI CITY: THE RISKS OF TUBERCULOSIS DISEASE - La Djabo Buton; Fitri Rachmillah Fadmi (STIKes Mandala Waluya Kendari, 2020)
Background: Tuberculosis is a contagious disease that is still a problem in the world today, not only in developing countries but also in developed countries. Likewise in Kendari City in 2012 - 2017. Efforts that can be made to prevent the increasing number of tuberculosis cases in the future is to make predictions. This study aims to determine the time series analysis in predicting the incidence of tuberculosis by sex and working area of ??health centre in the city of Kendari in 2018-2022. Methods: This type of research is quantitative descriptive with times series analysis design. The source of the research data was obtained from the Kendari City Health Institution, Southeast Sulawesi Province, namely the data on the case of pulmonary TB which included the gender and working area of ??the Health Centre in 2012 - 2017 in the city of Kendari to be processed and analyzed in time series using the trend method approach into 3 models. linear trend, quadratic trend, and an exponential trend. Results: The results showed that the best model for the prediction of pulmonary TB cases in Kendari City was the quadratic model. Cases of tuberculosis by sex are predicted to decrease in the period 2018 to 2022, with an average decline with an average decrease of 79 cases in men and 286 cases in women. Pulmonary TB cases based on the health centre area are predicted to experience an increase in cases from 2018 until 2022 with the highest average increase being in the Kemaraya Health Centre area. While the highest average decrease in cases in the area of ??the Eye Health Center. It is expected to become information for policymakers so that prevention and promotion efforts can be made early to the community. Conclusion: Based on the results of the study, the conclusion of this study is the Science, knowledge about risk and Patient Contact History is a risk factor for tuberculosis in the work area of Puuwatu Health Centre, Kendari City.